Prerequisites for Successful Milestones Implementation in Graduate Medical Education - Jennifer DiPace; Boyd Richards; Steve Paik (Association of American Medical Colleges, 2015)
Abstract This team-based learning (TBL) exercise, targeted toward program directors, associate program directors, and clinical competency committee members of all disciplines, is designed to engage the audience in discussions surrounding the practical implementation of milestones-based assessments of learners within their own programs. Through individual and group readiness assurance tests, the audience will review basic concepts of the ACGME's Next Accreditation System. Through a case study of fictional residency programs, the groups will explore best practices of clinical competency committee organization and structure, discuss attributes of reliable assessments needed to support the clinical competency committee's decisions, and share ways to use outcomes of the clinical competency committee for resident and program improvement. TBL is utilized as an instructional method based on its ability to promote discourse among audience members and to learn from each other. The resource includes an advanced preparation assignment, an individual readiness assurance test (RAT), a group RAT, a RAT answer key, and an application exercise. Evaluations completed by participants of this TBL exercise demonstrated that approximately 80% of respondents found the topic was timely, meaningful, and stimulating. Subjectively, in our own institution's graduate medical education community, the authors have found that this team-based learning session promoted collaboration amongst program leaders that has continued to grow over the months after the session.